The presence of thermal, shot, impulsive and flicker noise at millimeter-wave frequencies - Amca, Hasan A. (Institute of Electrical and Electronics Engineers Inc., 2019)
To meet the target demands in capacity, spectral efficiency, power efficiency and latency for the future mobile communications systems, a wide range of research is being carried out and many different scenarios are being considered. One of the most likely scenarios is the deployment of small-cells in the future 5G network that rely on the allocation of new frequencies around 30 GHz, which are referred to as mmWave frequencies. However, the noise and interference characteristics of these spectral regions need to be irrigated further before a new research begins. This article therefore analyses the behavior of the mm Wave frequencies with regards to the thermal noise, Shot Noise, Impulsive Noise and Flicker Noise behavior at the mm Wave frequencies in the context of future mobile communications systems such as 5G. © 2019 IEEE.
2019 International Symposium on Networks, Computers and Communications, ISNCC 2019 -- 2019-06-18 through 2019-06-20 -- Istanbul -- 155052
Keywords: Flicker; Frequency; Impulsive; Man-made; Mm Wave; Natural; Noise; Shot; Thermal